2017
DOI: 10.1016/j.ijvsm.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electroscalpel incisional wound healing potential of honey in wistar rats

Abstract: Electrosurgery reduces surgical bleeding, and delayed wound healing. This study evaluated comparative incisional wound healing potential of honey in wound created with electroscalpel and cold scalpel. The study used twelve (12) adult male albino rats (130 ± 20 g), randomly grouped into Electro-cautery (n = 6) and Cold scalpel (n = 6). Each rat had three full thickness (6 mm diameter) skin wounds (a, b and c) created on its dorsum with either Electroscalpel (ES) or Cold blade scalpel (CS), and treated topically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
9
0
2
Order By: Relevance
“…This was done with the aid of Imito Measure® Application (Imito AG, Flüelastrasse, Zürich, Switzerland) and the Java-based Image Processing and Analysis software, ImageJ Software (National Institutes of Health, USA). The time-course of cutaneous wound healing was determined as the wound contraction or closure rate using the formula [ 36 ]: where WC = Wound Contraction, WA = Wound Area, d 0 = Day 0 and d n = Day n or any other day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was done with the aid of Imito Measure® Application (Imito AG, Flüelastrasse, Zürich, Switzerland) and the Java-based Image Processing and Analysis software, ImageJ Software (National Institutes of Health, USA). The time-course of cutaneous wound healing was determined as the wound contraction or closure rate using the formula [ 36 ]: where WC = Wound Contraction, WA = Wound Area, d 0 = Day 0 and d n = Day n or any other day.…”
Section: Methodsmentioning
confidence: 99%
“…The wounds were evaluated in vivo on day 0, 2, 5, 7, 9, day 13, 15, and on day 21 for cutaneous wound healing indices such as Exudation, Edge edema; Hyperemia, and Granulation Tissue deposition based on methods described by Gupta et al (2011) [35] and subsequently modified by Eyarefe et al(2017 ) [36]. Wound Exudation, Wound Edge Edema; Wound Hyperemia was scored by two blinded pathologists working independently as 0 = Absent, 1-2 = Mild, 3-4 = Moderate, 5-6 = Severe.…”
Section: Assessment Of Macroscopic Wound Healing Indicesmentioning
confidence: 99%
“…Moreover, a recent study had shown enhanced healing of electroscalpel-induced wound of Wistar rats by EBH treatment, as compared to silver sulfadiazine which is being used as positive control [68]. Another in vivo study also proved that oral administration of EBH to measure the healing of colonic anastomosis in rats, had shown increment of the tensile strength measured by bursting pressure, increased fibroblast count and lowered mean of inflammatory cells count in rats supplemented with honey after the surgical procedure in comparison with the control group [70, 102].…”
Section: Therapeutic Effects Of Stingless Bee Honey and European Bmentioning
confidence: 99%
“…Essa propriedade é amplamente fundamentada na literatura científica e considerada uma das propriedades medicinais mais antigas descobertas na utilização dessa matéria-prima no âmbito medicinal. Tal propriedade está relacionada com as atividades imunoestimuladoras do mel no crescimento celular epitelial e do tecido conjuntivo, além de também atuar no desenvolvimento de novos capilares 35 . Outra linha terapêutica que vem sendo indicada como potencial para utilização do mel é a do tratamento adjuvante para tumores cerebrais uma vez que a utilização desse produto apresentou resultados promissores em um efeito antiproliferativo e antimetastático das células tumorais 31 .…”
Section: Discussionunclassified